2020
DOI: 10.1016/j.celrep.2020.108245
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Acute Kidney Injury Is Mediated by Nox4-SH3YL1

Abstract: Highlights d H 2 O 2 generation is mediated by interaction of Nox4 with p22 phox -SH3YL1 d SH3YL1-Nox4 regulates pro-inflammatory cytokine production and tubular damage d SH3YL1-Nox4 complex plays an important role in LPSinduced acute kidney injury

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…The antioxidant enzyme HO-1 also plays an important role in LPS-induced renal injury [23,24]. Here, we observed that LPS-injected mice exhibited increased expression of NOX4 in the kidneys, which is consistent with previous studies [21,22]. In addition, HO-1 expression was also increased in LPS-injected mice compared to control mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The antioxidant enzyme HO-1 also plays an important role in LPS-induced renal injury [23,24]. Here, we observed that LPS-injected mice exhibited increased expression of NOX4 in the kidneys, which is consistent with previous studies [21,22]. In addition, HO-1 expression was also increased in LPS-injected mice compared to control mice.…”
Section: Discussionsupporting
confidence: 92%
“…Molecules 2020, 25, x FOR PEER REVIEW 5 of 14 (GSH)/oxidized glutathione (GSSG) ratio, an indicator of oxidative stress, was decreased in the kidneys of LPS-injected mice, which was significantly reversed by apamin ( Figure 5D). Nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) produces reactive oxygen species (ROS) and contributes to LPS-induced oxidative stress in the kidney [21,22]. In addition to the pro-oxidant enzyme NOX4, heme oxygenase-1 (HO-1) also plays an important role as a stress-inducible antioxidant enzyme in oxidative stress caused by LPS [23,24].…”
Section: Apamin Suppressed Lps-induced Oxidative Stressmentioning
confidence: 99%
“…However, in obesity-caused renal vascular endothelial damage, O 2 − produced by NOX2 plays a more important role (150). In mouse renal TECs, Yoo et al (151) confirmed that LPS stimulation led to enhanced interaction between SH3YL1 and the anchoring protein P22phox of NOX4, thereby further activating NOX4 and leading to oxidative damage in the cells. In a CLP-induced AKI model, Angara Sureshbabu et al (128) found that necroptosis was activated in kidney cells, and co-immunoprecipitation (co-IP) demonstrated that RIPK3 could directly bind and stabilize NOX4, independent of its downstream signal, MLKL.…”
Section: Mitochondria and Oxidative Stress/nitrosative Stressmentioning
confidence: 98%
“…NADPH oxidases are a major source of reactive oxygen species (ROS) in the kidney in normal and pathological conditions (Sedeek et al 2013). Among NADPH oxidase isoforms, NADPH oxidase4 (NOX4), which regulates oxidative stress, is highly expressed in the kidney and has an important role in kidney diseases (Yoo et al 2020). We previously found that NOX4 aggravated kidney injury by promoting ROS-mediated programmed cell death and in ammation (Wang, Yang 2020b, Meng et al 2018).…”
Section: Discussionmentioning
confidence: 99%